2021
DOI: 10.3390/jof7090687
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Plant Defenses against Ophiostoma novo-ulmi by Elm (Ulmus minor Mill.) Fungal Endophytes

Abstract: Some fungal endophytes of forest trees are recognized as beneficial symbionts against stresses. In previous works, two elm endophytes from the classes Cystobasidiomycetes and Eurotiomycetes promoted host resistance to abiotic stress, and another elm endophyte from Dothideomycetes enhanced host resistance to Dutch elm disease (DED). Here, we hypothesize that the combined effect of these endophytes activate the plant immune and/or antioxidant system, leading to a defense priming and/or increased oxidative protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 107 publications
2
7
0
Order By: Relevance
“…PLDβ1 expression is repressed by salicylic acid (SA), and the mutation of PLDβ1 enhanced SA production and signaling pathways upon pathogen infection [49,50]. On the other hand, PR4 and PR5 (thaumatin 1) genes were significantly upregulated in the resistant genotype, suggesting that resistance to DED in U. americana could be attributed to the simultaneous activation of SA and JA signaling, which agrees with previous findings [9,17]. Hence, it may be inferred that in the American elm-Onu pathosystem, the RPM1-mediated activation of ETI and repression of the PLDβ1 might be crucial for the resistance, and that the Onu pathogen might induce the PLDβ1 in the susceptible, leading to the disease development.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PLDβ1 expression is repressed by salicylic acid (SA), and the mutation of PLDβ1 enhanced SA production and signaling pathways upon pathogen infection [49,50]. On the other hand, PR4 and PR5 (thaumatin 1) genes were significantly upregulated in the resistant genotype, suggesting that resistance to DED in U. americana could be attributed to the simultaneous activation of SA and JA signaling, which agrees with previous findings [9,17]. Hence, it may be inferred that in the American elm-Onu pathosystem, the RPM1-mediated activation of ETI and repression of the PLDβ1 might be crucial for the resistance, and that the Onu pathogen might induce the PLDβ1 in the susceptible, leading to the disease development.…”
Section: Discussionsupporting
confidence: 89%
“…The induction of defense-related genes and plant hormone jasmonic acid (JA) during the necrotrophic phase of DED has also been characterized as a resistance mechanism by comparing resistant and susceptible U. americana genotypes. Furthermore, at the early stage of DED, the application of salicylic acid (SA) enhanced elm resistance in the field and indicated that the coordinated action of SA and JA might be crucial in DED, as reported for resistance to diseases caused by other hemibiotrophic pathogens [9,17,18]. Despite these efforts toward dissecting the defense mechanisms against DED, the molecular responses of resistant and susceptible American elm genotypes to DED at the whole-transcriptmic level are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced pathogen proliferation in this genotype may be indicative of and partly explain its high DED-resistance level. This result supports a recent work where higher O. novo-ulmi dispersal was observed in M-DV1 than in M-DV2.3 plants (Martínez-Arias et al 2021a), indicating a consistent behavior of M-DV2.3 in limiting O. novo-ulmi spread when compared to other genotypes, possibly because this genotype develops vessels of smaller diameter (Pita et al 2018) and length (authors, unpublished results). In turn, colonization of plants by P5 was rather similar in all elm genotypes, with the exception of the susceptible M-DV1, whose roots showed higher presence of P5.…”
Section: P5 Endophytic Yeast Hindered Colonization Of Elm Plantlets B...supporting
confidence: 90%
“…Endophytes possess mechanisms such as exoenzymes to allow them access to these strengthened cells, but the deposits may prevent pathogens from doing the same [ 71 ]. Endophytes can also act as priming stimuli that induce plant defence responses through transcriptional reprogramming; for example, by modulating the expression of downstream defence-related genes such as those involved in salicylic acid, jasmonic acid and ethylene signaling pathways [ 70 , 73 , 74 , 75 , 76 ]. Colonization by endophytes (and pathogens) and subsequent metabolite secretion have also been associated with increasing the rate of photosynthesis ( Sclerotinia sclerotiorum ), chlorophyll content of plant cells, density of trichomes and stomata on plant tissues ( Beauveria bassiana ), antioxidant enzyme activity, callose deposition, cell lignification and phytoalexin accumulation ( Diaporthe liquidambaris ) [ 70 , 73 , 77 ].…”
Section: Fungal Endophytes and Their Effects On Fungal Pathogensmentioning
confidence: 99%